Self-sovereign identity on the blockchain: contextual analysis and quantification of SSI principles implementation - Pava-Díaz, Roberto A.; Gil-Ruiz, Jesús; López-Sarmiento, Danilo A. (Frontiers in Blockchain, 2024)
Self-sovereign identity (SSI) embodies the fundamental human right to own and control a digital identity that grants access to public, social, and financial services. The absence of a dedicated digital identity layer in the development of the Internet has rendered SSI a significant challenge in contemporary society. Blockchain technology emerges as a promising solution by enabling the creation of decentralized and automatically verifiable identities. This study contextualizes SSI and analyzes how blockchain technology facilitates the autonomous management of digital identities. It explores nine prominent frameworks in this field -Sovrin, uPort, Jolocom, Shocard, Litentry, Civic, Kilt, Idena and ION -highlighting their features, functionalities, and compliance with digital identity principles. The research concludes by identifying the challenges and opportunities in implementing these systems for digital identity management, thus contributing to the advancement of this emerging field.